Analysis of Opportunities and Threats of Trade in Indonesian Textile Products with Australia: Case Study in the APEC Framework - Novi Rudiyanti; Daspar (JISOSEPOL: Jurnal Ilmu Sosial Ekonomi dan Politik, 2025)
This study offers an in-depth examination of the opportunities and challenges Indonesia faces in its textile trade with Australia, particularly within the framework of regional economic cooperation under APEC (Asia-Pacific Economic Cooperation). Employing a descriptive qualitative approach, the research explores various factors that influence Indonesia’s textile export performance, including the impact of the Indonesia-Australia Comprehensive Economic Partnership Agreement (IA-CEPA). The findings reveal that Indonesia holds considerable potential to expand its textile market in Australia. However, several obstacles remain, such as competition from major textile-exporting countries like China and Vietnam, as well as increasing demands from the Australian market regarding sustainability and product quality. In response to these challenges, the study recommends strengthening Indonesia’s competitiveness through improved product quality, design innovation, market diversification, and closer collaboration between the government and private sector to promote environmentally friendly production practices.